Policy Provisions and Implementation of Seed Technology Research, and Innovation in Nepal - Timsina, Krishna; Gauchan, Devendra; Basi, Sabin; Jaishi, Mahesh; Pandey, Sunita (Nepal Public Policy Review, 2023)
Favorable policy provisions and their effective implementation are critical in promoting agricultural research innovation and technology development for ensuring food security and livelihood improvement of the farmers. This paper aims to (i) review current policy provisions made for research and innovations in the seed sector; (ii) assess its implementation status as envisaged in the policies and (iii) identify issues and gaps to make recommendations for potential policy solutions. The study employed a three-step process which included listing and review of the policies, followed by an assessment of their implementation status by developing a policy framework. The study showed that most policy documents have emphasized increasing production and productivity in agriculture, but have undermined the importance of research and technology to enhance agricultural productivity. In addition, current challenges such as nutritional security, natural resource management, and climate change have not been given adequate space in policy design. Very few policy documents have focused to develop climate-resilient varieties, breeds and technologies. Policy provisions for investment in agriculture research and innovation are inadequate and fragmented, despite their significant role in achieving a high rate of return in agriculture development. Analysis showed that investment, human resource development and institutional frameworks are weak, but the policy framework sounds relatively good. Therefore, it is urgent to manage human resources and investment as well as develop new provincial and local government agricultural policies and institutional frameworks aligned with federal policy considering the issues and challenges being faced in the present and what may happen in future. Increased investment and capacity development in plant breeding, modern technology, and seed system; facilitating public-private partnership and private sector to attract research investment; participatory and decentralized variety selection, release and recommendation; coordination mechanism for policy formulations and implementation; and provide incentives for research, release and promotion of domestically developed varieties are recommended to strengthen the variety and seed system innovations in Nepal.